Ultralow-Power Near Infrared Lamp Light Operable Targeted Organic Nanoparticle Photodynamic Therapy - Huang, Ling; Li, Zhanjun; Zhao, Yang; Zhang, Yuanwei; Wu, Shuang; Zhao, Jianzhang; Han, Gang (Journal of the American Chemical Society, 2016)
Tissue penetration depth is a major challenge in practical photodynamic therapy (PDT). A biocompatible and highly effective near infrared (NIR)-light-absorbing carbazole-substituted BODIPY (Car-BDP) molecule is reported as a class of imaging-guidable deep-tissue activatable photosensitizers for PDT. Car-BDP possesses an intense, broad NIR absorption band (600–800 nm) with a remarkably high singlet oxygen quantum yield (ΦΔ = 67%). After being encapsulated with biodegradable PLA–PEG-FA polymers, Car-BDP can form uniform and small organic nanoparticles that are water-soluble and tumor-targetable. Rather than using laser light, such nanoparticles offer an unprecedented deep-tissue, tumor targeting photodynamic therapeutic effect by using an exceptionally low-power-density and cost-effective lamp light (12 mW cm–2). In addition, these nanoparticles can be simultaneously traced in vivo due to their excellent NIR fluorescence. This study signals a major step forward in photodynamic therapy by developing a new class of NIR-absorbing biocompatible organic nanoparticles for effective targeting and treatment of deep-tissue tumors. This work also provides a potential new platform for precise tumor-targeting theranostics and novel opportunities for future affordable clinical cancer treatment.